FACTORS ASSOCIATED WITH DEPRESSION AMONG CHRONIC KIDNEY DISEASE PATIENTS RECEIVING HEMODIALYSIS - Isdiana, Dini Fitria; Mugi Hartoyo; Umi Margi Rahayu; Rodhi Hartono; Budiyati (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
Chronic kidney disease (CKD) is one of the therapies for CKD is hemodialysis. Hemodialysis can have psychological effects, one of which is depression. The purpose of this study was to identify factors associated with depression in patients with chronic kidney failure undergoing hemodialysis. This is a quantitative study with a descriptive correlational design using a cross-sectional design on 52 samples with purposive sampling. The study was conducted using the Beck Depression Inventory II questionnaire, Fatigue Severity Scale, Pittsburgh Sleep Quality Index, and data were tested using Kendall's Tau b and c tests and Ordinal Logistic Regression. The study found that 46.2% of CKD patients experienced severe depression. Depression was more prevalent among CKD patients aged 41–55 years (40.0%), females (61.5%), married individuals (65.4%), those with a high school education (40.4%), those who had undergone hemodialysis for 13–36 months (44.2%), respondents with poor sleep patterns (55.8%), and those with comorbid conditions (hypertension) (34.6%). The results of Kendall's tau analysis showed that factors associated with depression include age, gender (p=0.001), marital status (p=0.001), duration of hemodialysis (p=0.016), education (p=0.001), sleep patterns (p=0.001), fatigue (p=0.001), and comorbidities (p=0.001), while age did not show a significant association (p=0.057). Among the factors analyzed using the partial test, no single factor was dominant in influencing depression levels in CKD HD patients. The odds ratio for education was the highest, with a value of 603,801.0287. Clinically, the odds ratio results indicate that education is the dominant factor, with a 60-fold influence on depression in CKD HD patients.